Análisis bibliométrico, tecnologías disruptivas y gerencia de las instituciones educativas: una revisión de scopus y wos en el último quinquenio - Claudia Liliana Serrano Junco; Julián Alberto Agudelo Idárraga; Andrea del Pilar García Donato (Mundo Fesc)
The mechanisms used for the management and coordination of administrative processes in the management of educational institutions have acquired a relevant importance over time, especially when the use of disruptive technologies is adopted in these processes as a performance or action that technifies, improves and facilitates said processes, since it allows a transformation for educational quality and decision-making; in turn, Information and Communication Technologies have transformed the way education is taught, they have opened up new possibilities for learning and teaching. It is significant to highlight that the productivity of organizations achieves an important technological influence configuration [1]. The present study emerges as a result of the relevance and interest of the subject today, contributing to the disciplinary area, based on an analysis and review of literature registered in the WoS and Scopus databases between the years 2019 and 2023, whose main objective is to identify which are the studies carried out in this disciplinary field and what are the research trends. Through a systematic review of information, the authors, articles, and journals with the greatest influence on research were identified. The cocitation network and the most influential authors were identified using a mixed-descriptive approach that allows for the interrelation of the aforementioned elements. Finally, a semantic categorical tree was developed, identifying the ontological, structural, and guiding or current authors. In turn, the clusters related to driving, niche, and emerging topics were classified, concluding the current state of the discipline of the use of disruptive technologies for educational management.